Communicate the results of an architectural research: How to design a digital scientific article in the architectural field - Castro Marcucci, Andrea (Universidad ORT Uruguay, 2021)
The scientific paper is the preferred form in which advances in any field of science are communicated. The publishing of scientific journals has undergone a digital transformation, even in areas such as architecture, where this process has paradoxically been slow. However, papers that make in architectural journals are still written and published as if they were still in a printed format, the conventional system inaugurated by Gutenberg. Such traditional publications are limited into two-dimensional format, which does not recognize the way of communicating ideas in architecture. This article explores the possibilities of this new digital format, closer to the architectural gesture, which, while valuing traditional forms such as sketches, plans or photographs, incorporates new possibilities offered by digital magazines such as digital models and evolving infographics. These types of projective representations multiply the communication possibilities of researchers and creators. As a result, the contemporary paper can and should be representative of the innovation that underlies its existence. Its content is a vivid reflection of the natural evolution of architectural, urban or landscape research. This makes it necessary for the scientific paper to include new types of dynamic formats. This article presents some of these formats and methods for communicating the results of architectural research today: hypertexts, embedded resources, geo-referenced images, 3D models and linked bibliography, among others. This article is in turn an invitation to the authors to enrich their practices with the resources of visual, graphic and textual language.